Googling Musculoskeletal-Related Pain and Ranking of Medical Associations’ Patient Information Pages: Google Ads Keyword Planner Analysis - Yamaguchi, Yoichiro; Lee, Deokcheol; Nagai, Takuya; Funamoto, Taro; Tajima, Takuya; Chosa, Etsuo (Journal of Medical Internet Research, 2020)
Most people currently use the internet to obtain information about many subjects, including health information. Thus, medical associations need to provide accurate medical information websites. Although medical associations have their own patient education pages, it is not clear if these websites actually show up in search results. The aim of this study was to evaluate how well medical associations function as online information providers by searching for information about musculoskeletal-related pain online and determining the ranking of the websites of medical associations. We conducted a Google search for frequently searched keywords. Keywords were extracted using Google Ads Keyword Planner associated with "pain" relevant to the musculoskeletal system from June 2016 to December 2019. The top 20 search queries were extracted and searched using the Google search engine in Japan and the United States. The number of suggested queries for "pain" provided by Google Ads Keyword Planner was 930 in the United States and 2400 in Japan. Among the top 20 musculoskeletal-related pain queries chosen, the probability that the medical associations' websites would appear in the top 10 results was 30% in the United States and 45% in Japan. In five queries each, the associations' websites did not appear among the top 100 results. No significant difference was found in the rank of the associations' website search results (P=.28). To provide accurate medical information to patients, it is essential to undertake effective measures for search engine optimization. For orthopedic associations, it is necessary that their websites should appear among the top search results.